Micro-PET Imaging Demonstrates 3-O-β-D-Glucopyranosyl Platycodigenin as an Effective Metabolite Affects Permeability of Cell Membrane and Improves Dosimetry of [18F]-Phillygenin in Lung Tissue - Shen, Fukui; Wu, Wenbo; Zhang, Man; Ma, Xiaoyao; Cui, Qingxin; Tang, Zhongyao; Huang, Hao; Tong, Tiantian; Yau, Leefong; Jiang, Zhihong; Hou, Yuanyuan; Bai, Gang (Frontiers in Pharmacology, 2019)
Platycodon grandiflorum, as a traditional medicinal plant, is commonly used in the treatment of pulmonary disease. Platycodon saponins are proposed as active ingredients. However, the role of secondary saponin metabolites (SSM) in the traditional use of Platycodon has not yet been fully clarified. In this study, [18F]-phillygenin ([18F]-PH) probe was synthesized and thereby used as a tracer for micro-positron emission tomography scanning to explore the effects of platycodon saponins. The membrane permeability with different SSM was evaluated in vitro based on the dye carrying capacity of fluorescein isothiocyanate. The results showed that total platycodon saponins improved the dosimetry of [18F]-PH in the lung tissue, and an SSM named 3-O-β-D-glucopyranosyl platycodigenin (GPD682) appreciably changed the distribution of drugs both in vitro and in vivo. We propose that GPD682 could be utilized as an important ingredient to help drug delivery to the lung tissue and improve the treatment of respiratory disease.